Pengaruh Beban Kerja, Gaya Kepemimpinan dan Stres Kerja terhadap Kinerja Karyawan (Studi Pada Toko Citra Tekstil Malang) - Dinda Yulian Triasa; Abdul Kodir Djaelani; Khalikussabir Khalikussabir (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract This research is to identify and analyze the effect of workload, leadership style and work stress on employee performance in the case of Citra Textile Stores Malang. The population in this study were employees of Citra Textile Store Malang. The sample in this study were 126 employees of Citra Textile Store Malang, with the determination of the number of samples using the slovin formula, which then obtained a total of 96 respondents. The analysis technique uses multiple linear regression analysis. The results simultaneously and partially showed that workload, leadership style and work stress have a positive and significant effect on employee performance. Keywords: Workload, Leadership Style, Work Stress, Employee Performance